The Role of Geographic Information Systems (GIS) in Location-Based Decision Making - Khairul Akmal (STMIK Indonesia Banda Aceh, 2023)
Geographic Information Systems (GIS) play a crucial role in location-based decision making in various contexts. The aim of this research is to investigate how GIS contributes to improving the decision-making process by considering spatial factors. The research method used involves in-depth literature analysis as well as case studies to illustrate the application of GIS in the context of location-based decision making. The analysis results show that GIS provides advantages in visualizing geographic data, analyzing spatial patterns, and facilitating the integration of various information to support a more effective decision-making process. The conclusion of this research is that the application of GIS can increase efficiency and effectiveness in location-based decision making, both in the context of business, government and natural resource management.